2009
DOI: 10.1007/s11605-009-1003-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Gastric Acid Secretion and the Risk to Develop Barrett’s Esophagus After Esophagectomy for Chagasic Achalasia

Abstract: Barrett's esophagus in the esophageal stump was associated to high preoperative levels of gastric acid secretion, serum pepsinogen, and also gastritis in the transposed stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Therefore, the pH was higher than that in the common theory due to intestinal juices. It has been shown that acid output inhibition is enough to prevent the development of esophagitis [37], and gastric acid is considered essential to esophagus damage [38]. The results of this study suggest that ECQ show efficacy on the development of reflux esophagitis by the inhibition of gastric secretion.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, the pH was higher than that in the common theory due to intestinal juices. It has been shown that acid output inhibition is enough to prevent the development of esophagitis [37], and gastric acid is considered essential to esophagus damage [38]. The results of this study suggest that ECQ show efficacy on the development of reflux esophagitis by the inhibition of gastric secretion.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, we cannot say with certainty that the enlarged proximal gastrectomy contributed to the reduction of esophagitis and Barrett in our patients. Other authors also found the occurrence of esophagitis and Barrett's esophagus in the esophageal stump of patients with gastric tube, since its vertical position is maintained, facilitating rapid gastric emptying, as well as duodenogastric reflux 34,35,38,39 . We conducted esophagectomy with enlarged proximal gastrectomy (gastric tube) and yearly endoscopy, as experts recommend.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 92%
“…Considering that in these patients, basal and stimulated acid secretion is lower than that found in normal subjects, and the right colon may be affected by the disease, reconstitution with the stomach initially appeared to be a great option. However, the follow-up of patients submitted to esophagectomy with this type of reconstitution and without the use of proton pump inhibitor (PPI) may show disastrous complications, such as Barrett's esophagus and esophageal stump cancer 25,[33][34][35] .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative and postoperative gastric acid secretion has been identified as a potential influence on the development of post‐esophagectomy Barrett's. A single study that addressed this issue was identified . Thirty‐eight patients with end‐stage achalasia underwent presurgical and post‐surgical measurement of basal and stimulated gastric acid secretion.…”
Section: Association With Gastric Acid Secretion and Ppi Usementioning
confidence: 99%